SYSTEM OF THE REMOTE ACCESS VIA INTRANET/INTERNET TO THE DIGITAL SIGNAL PROCESSOR DSP56307 TO DEBUG PROGRAMS, LEARN THE PERIPHERALS AND REALIZE DIFFERENT EXPERIMENTS - Tsidelko, Vladislav; Karpa, Victor (International Journal of Computing, 2014)
System of the Remote Access via Intranet/Internet to the digital signal processor DSP56307 allows to debug programs, learn the peripherals and realize different experiments of the using this processor. The worked out system represents the software/hardware complex which include three components: client, server and six working stations. Debugging module of the working station includes two DSP56307EVM which gives the opportunity to learn the peripherals of this processor really for the first time (interfaces HOST, ESSI, SCI and timer). Virtual instruments on the client side (generator, oscilograph, spectrum analyzer) give the opportunity to realize the experiments of using the DSP in the regime of the FFT, digital filtering, generation of the signals, etc. There are two regimes of the working of the system: a) N-clients – one working station; b) N-clients – six working stations.